Analisis Pengaruh Pengetahuan Barang Berbahaya (Dangerous Goods) Terhadap Perilaku Keselamatan Penerbangan di Bandar Udara El-Tari Kupang Nusa Tenggara Timur - Nova Vita Devi Domi; Dhiani Dyahjatmayanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Every air traveler needs to understand the importance of dangerous goods. By understanding the nature and risks of these items, precautions can be taken to prevent accidents and ensure safe travel for all. In practice, numerous passengers have experienced delays at security checkpoints due to carrying prohibited or restricted items such as lighters, sharp tools like scissors, aerosols, and high-capacity power banks. These incidents not only disrupt airport operations but also highlight gaps in public awareness regarding aviation safety regulations.This study aims to examine the influence of knowledge about dangerous goods on flight safety, with a focus on passengers traveling through El-Tari Airport in Kupang, East Nusa Tenggara. A quantitative research method was employed by distributing 100 structured questionnaires to respondents using purposive sampling, targeting passengers with prior flight experience. Data analysis techniques included simple linear regression, T-tests, and the coefficient of determination (R²) to assess the relationship between knowledge levels and safety behavior. The findings show that knowledge about dangerous goods (variable X) significantly influences passenger safety behavior (variable Y), evidenced by a p-value of 0.000. This indicates a strong and positive correlation, where better knowledge leads to more responsible behavior during air travel. The R-square value of 0.530 suggests that 53% of variations in safety behavior can be explained by knowledge, while the remaining 47% may be influenced by other factors such as attitudes, past experiences, signage visibility, and staff communication.These findings underscore the urgent need for intensified public education efforts at airports through visual campaigns, digital information, and pre-flight reminders. Improving passenger knowledge about dangerous goods can significantly enhance overall flight safety and reduce the risk of delays or violations. Future research could explore the role of demographic factors or the effectiveness of current educational strategies.